MELTING EXPERIMENTS ON HOMOGENEOUS MIXTURES OF PERIDOTITE AND BASALT: APPLICATION TO THE GENESIS OF OCEAN ISLAND BASALTS - Kogiso T.; Hirose K.; Takahashi E. (My University, 1998)
Melting experiments on synthesized homogeneous mixtures of a pyrolitic peridotite (KLB-1) and average mid-oceanic ridge basalt (MORB) were carried out at pressures between 1.5 and 3.0 GPa and temperatures between 1300° and 1525°C with a piston-cylinder apparatus. Melt compositions were determined using the diamond aggregate method. Partial melts produced from the peridotite-basalt mixtures have higher FeO, TiO2 and alkali elements and similar or lower SiO2 relative to those from pyrolitic peridotite. This is generally consistent with the results of previous experimental studies and prediction of melting model calculations. Our results indicate that peridotite-basalt mixtures tend to produce silica-undersaturated magmas enriched in Fe and Ti even at moderate degrees of melting. In particular, partial melts produced at 3.0 GPa coexist with garnet and are similar in composition to those of alkali basalts which commonly occur in shield-building stages of ocean island volcanoes. Melting of peridotite-basalt mixtures is consistent with the general characteristics of ocean island basalts (OIBs) such as enrichment in Fe and Ti relative to MORB, predominance of alkali basalts, and trace element features indicating garnet-present melting. This suggests that the source mantle of OIBs is generally more enriched in a basaltic component than pyrolitic mantle. It has been proposed that tholeiitic magmas in ocean islands and continental flood basalts can be produced by melting of heterogeneous plumes including recycled basaltic crust. Our results imply that alkali basaltic magmas can also be produced from such heterogeneous mantle plumes. Therefore partial melting of mantle plumes including recycled basaltic crust can produce the major element diversity in OIBs, although it is difficult to explain the high-CaO signature of HIMU basalts.
Keywords: PARTIAL MELTING; EXPERIMENTAL STUDIES; MAJOR ELEMENTS; ALKALI BASALTS; MANTLE PLUMES